Eye of the storm - Higgins, Jack, 1929- (New York : Berkley Books, 1993)
Martin Broson is recruited by British Intelligence to catch a master terrorist whose goal is to launch a mortar against the War Cabinet at a meeting at 10 Downing Street.
Booklist.
Publisher's Weekly.
Wilson's Fiction.
Adult
Keywords: Adventure stories; Spy stories; Terrorism -- Fiction; Adventure fiction; Spy stories; Terrorism -- Fiction